Polisemi Leksem Qi dalam Bahasa Mandarin - Taufiq, Tania (Program Studi Pendidikan Bahasa Mandarin, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2022)
Polysemy is a lexeme that has a number of related meanings. Lexeme qi is a polysemous lexeme in Chinese. This research is aimed to determine and explain the components of meaning shared by lexeme qi’s meanings. It is also to determine the contributions of meaning in the lexeme’s compound words. The research method used is the descriptive qualitative method and Nida’s Theory of Componential Analysis of Meaning (1975) is used for data analysis. The data used are the lexeme qi’s 11 meanings and 16 of its compound words from Xiandai Hanyu Cidian Dictionary (2016). In conclusion, it is discovered that there are two common components shared by the 11 meanings of the lexeme qi, namely, [+action] and [+change of state]. Furthermore, there are only 7 meanings of the lexeme qi that is represented in the 16 compound words studied.